The Efforts of Principals as Innovators in Increasing Teacher Creativity in MAN 1 Madiun - Heru Saiful Anwar; Ahmad Bashori (Educan : Jurnal Pendidikan Islam, 2019)
The progress of an educational institution wherever its location is greatlyinfluenced by the quality and professionalism of the principal in leading, especiallyleading school personnel, both educators and education personnel. The purpose ofthis writing is: (1) to find out how the principal's efforts as an innovator inincreasing teacher creativity in MAN 1 Madiun. (2) find out what are the factorsthat support the principal's efforts as an innovator in improving teacher creativity atMAN 1 Madiun. (3) find out what are the factors that hinder the principal's effortsas an innovator in increasing teacher creativity. This study uses descriptivequalitative research, with methods of collecting observation data, interviews, anddocumentation. As for the data analysis, using descriptive qualitative data analysis.This study concludes that: 1) Efforts of Principals as Innovators in ImprovingTeacher Creativity MAN 1 Madiun, namely: Provide opportunities for teachers toimprove their creation, Give rewards to outstanding teachers, Putting the teacher inaccordance with its potential, Include teachers in seminars and training, Providesufficient space for the teacher to develop himself through the MGMP, MaximizingPKG performance (teacher performance assessment). 2). Supporting Factors ofSchool Principals' Efforts as Innovators in Improving Teacher Creativity in MAN 1Madiun, namely: Professional headmaster, Embedded culture competes with eachteacher. 3). Inhibiting Factors of School Principals' Efforts as Innovators inImproving Teacher Creativity MAN 1 Madiun, namely: self motivation as a part ofteachers who lack, Different abilities for each teacher, limited facilities andinfrastructure.